High refractive index polymers: fundamental research and practical applications - Liu, Jin-gang; Ueda, Mitsuru (Journal of materials chemistry, 2009)
Rapid developments in advanced photonic devices have led to the increasing exploration of high refractive index (high-n) materials, particularly high-refractive-index polymers (HRIP). High refractive indices have been achieved either by introducing substituents with high molar refractions to make intrinsic HRIPs or by combining high-n nanoparticles with polymer matrixes to make HRIP nanocomposites. For intrinsic HRIPs, aromatic rings, sulfur-containing groups, halogens except fluorine and organometallic moieties are often utilized to increase their refractive indices. However, their upper n limitation is usually below 1.80. Incorporation of high-n nanoparticles into polymers seems to be a more promising strategy to achieve a refractive index higher than 1.80; however, the obtained organic-inorganic hybrid materials sometimes suffer from poor storage stability, higher optical loss and poor processability. Besides the refractive index, optical dispersion (Abbe number), birefringence and optical transparency are often involved in designing HRIPs for practical optical fabrications. Therefore, research of HRIPs is becoming an interdisciplinary subject. This feature article reviews recent developments in optical HRIPs and their typical applications in high-tech fields.